Electron beam induced surface cross-linking of functional monomers coated on silicon substrate - Mahapatra, S. K.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A.; Bhoraskar, Vasant N. (Materials Letters, 2006)
A 3: 1 composition of functional monomer: multifunctional acrylate was spin coated and later cross-linked under the influence of keV electron irradiation on the surface of silicon to generate a surface-anchored cross-linked network bearing functional moieties. Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) as well as wetting angle measurements were used for the analysis of functional monomer cross-linked surfaces. Results of the surface reconstruction of surfaces and electron irradiated on coated silicon wafers reveal that long-term hydrophilic surfaces can be achieved. Thus, the surface architecture can be favorably manipulated by using this remarkable technique with a Suitable combination of functional monomers and cross-linkers. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: electron beam irradiation; FTIR; Polymers; surface modification; XPS

Irradiation effects of 12 eV oxygen ions on polyimide and fluorinated ethylene propylene - Majeed, Riyadh M A Abdul; Purohit, V. S.; Bhoraskar, S. V.; Mandale, A. B.; Bhoraskar, Vasant N. (Radiation Effects and Defects in Solids, 2006)
Polyimide (PI) and Fluorinated Ethylene Propylene (FEP) samples (15mm x 15mm x 50 mu m ) were exposed to atomic oxygen ions of average energy similar to 12 eV and flux similar to 5x10(13) ions cm(-2) s(-1) , produced in the Electron Cyclotron Resonance (ECR) plasma. The energy and the flux of the oxygen ions at different positions in the plasma were measured by a retarding field analyzer. The fluence of the oxygen ions was varied from sample to sample in the range of similar to 5x10(16) to 2x10(17) ions cm(-2) by changing the irradiation period. The pre- and the post-irradiated samples were characterized by the weight loss, Scanning Electron Microscopy (SEM), X-ray Photoelectron Spectroscopy (XPS), and Fourier Transform Infrared (FTIR) techniques. The weight of the PI and FEP samples decreased with increasing the ion fluence. However, the erosion yield for the PI is found to be higher, by almost a factor five, when compared with that of FEP. On the surface region of irradiated samples, the concentrations of the carbon, fluorine, and oxygen and their corresponding chemical bonds have changed appreciably. Moreover, blisters and nanoglobules were also observed even at a fluence of similar to 10(17) ions cm(-2) . This oxygen ion fluence is almost two orders of magnitude lower than that of the 5 eV atomic oxygen, which a satellite encounters in the space, at the low Earth orbit, during its mission period of about 7 years.
Keywords: atomic oxygen; ECR plasma; FEP; FTIR; Polyimide; SEM; weight loss; XPS